PRINCIPAL LEADERSHIP IN IMPROVING THE QUALITY OF EDUCATIONAL UNITS - Wahyu Priyanti (EDU RESEARCH, 2025)
Success a unit education is greatly influenced by leadership head school . In the context of improvement quality education , head school play a role as the mover the main capable create environment conducive learning . Research​ This aiming For analyze various leadership strategies head school in increase quality education in schools . Through approach qualitative , data collected from interview with head schools , teachers, and other stakeholders. Research results show that leadership head transformative , participatory and collaborative schools​ contribute significant to improvement quality Education . Head capable school​ motivating teachers, involving parents , and optimizing source existing power , shows​ more results​ Good in achievement academic students . Research This conclude that development competence leadership head school need become focus main in effort improvement quality unit education . It is hoped that the findings This can become reference for development policy more education​ effective.